Ericksonian hypnotherapy for selective mutism: A single-case study - Cavarra, Mauro; Brizio, Adelina; Gava, Nicoletta (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Children affected by selective mutism don’t speak in contexts that are unfamiliar to them or in which speaking is expected or required (e.g. school, kindergarten…). Such disorder interferes with the child’s normal activities, may have invalidating consequences in the long run if left untreated, is associated to anxious conditions and is considered hard to treat. Contemporary research is still in need of methodologically rigorous outcome studies and the results described in the small number of published randomized controlled trials and retrospective studies indicate cognitive-behavioral interventions lasting 20-24 sessions as the best therapeutic option. This case study, involving a 7-year-old girl, aims at providing preliminary evidence on the effectiveness of Ericksonian hypnosis in the treatment of this condition. A brief review of current evidence is provided. Methods: The case was treated by a licensed hypnotherapist, specialized in family therapy, in 5 sessions during the course of 3 months. Results: After 3 months the symptoms of the client were resolved and the diagnosis was no longer applicable. Other improvements regarded her mood, social skills and school performance. Conclusions: Ericksonian Hypnotherapy lead to the remission of the disorder and to the improvement of the general well being of the client in 5 sessions, a much briefer time span compared to what is reported in current literature. This paper represents the first step in the elaboration of replicable and reliable intervention principles.